Geographical Information Systems (GIS) and Multi-Criteria Decision Making (MCDM) methods for the evaluation of solar farms locations: Case study in south-eastern Spain - Sánchez-Lozano, Juan M.; Teruel-Solano, Jerónimo; Soto-Elvira, Pedro L.; Socorro García-Cascales, M. (Renewable & sustainable energy reviews, 2013)
This paper is based on the combination of a Geographic Information System (GIS) and tools or multi-criteria decision making (MCDM) methods in order to obtain the evaluation of the optimal placement of photovoltaic solar power plants in the area of Cartagena (Region of Murcia), in southeast Spain. The combination GIS–MCDM generates an excellent analysis tool that allows for the creation of an extensive cartographic and alphanumeric database that will later be used by multi-criteria methodologies to simplify problems to solve and promote the use of multiple criteria. In GIS two types of criteria will be reflected: constraints or restrictive criteria, and weighting criteria or factors. Constraints or restrictive criteria will make it possible to reduce the area of study by discarding those areas that prevent the implementation of renewable energy plants. These criteria will be obtained from the legislation (planning regulations, protected areas, road networks, railways, waterways, mountains, etc). Weighting criteria or factors will be those which, according to the objective to be reached, influence the ability to solve a concrete alternative. The choice of such criteria is marked by the influence presented to the overall goal; in this case they will be location, geomorphological, environmental and climatic criteria. Through the use of MCDM the criteria or factors mentioned will be weighted in order to evaluate potential sites to locate a solar plant. Analysis and calculation of the weights of these factors will be conducted using Analytic Hierarchy Process (AHP). The assessment of the alternatives according to their degree of adequacy is carried out through the TOPSIS method (Technique for Order Preference by Similarity to Ideal Solution).